Composition for inorganic powder injection molding, and molded and sintered bodies using the same

JP7652902B2Active Publication Date: 2025-03-27ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023536673
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-07-19
Filing Date
2022-07-01
Publication Date
2025-03-27
Estimated Expiration
2042-07-01

AI Technical Summary

Benefits of technology

【0021】 本発明によれば、無機粉末射出成形用途に適した変性ポリアセタールを含む組成物を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007652902000001
    Figure 0007652902000001
  • Figure 0007652902000002
    Figure 0007652902000002
  • Figure 0007652902000003
    Figure 0007652902000003
Patent Text Reader

Abstract

The purpose of the present invention is to provide a composition which contains a modified polyacetal and is suitable for inorganic powder injection molding. A composition for inorganic powder injection molding according to the present invention contains a sinterable inorganic powder and an organic binder which contains a modified polyacetal (C) that has a polyacetal segment (A) and a modification segment (B). With respect to this composition for inorganic powder injection molding, the number average molecular weight of the modification segment (B) is 500 to 10,000.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a molding material used in producing an inorganic powder sintered compact, and a molded body and a sintered body using the same. [Background technology]

[0002] Powder injection molding is known as a method for manufacturing metal and ceramic parts. In this method, a composition for inorganic powder injection molding is obtained by melting and kneading sinterable inorganic powder such as metal, ceramic, or cermet with an organic binder composed of an organic compound such as polyethylene, polypropylene, or paraffin wax, and then the composition is injection molded into a green molded body, after which the green molded body is subjected to a degreasing process to remove the organic binder components. Finally, the debindered molded body is sintered to obtain the desired part. This method has the advantages of being able to mass-produce parts with complex shapes at once, with a high degree of freedom in shape, a high degree of freedom in materials, high dimensional accuracy, and high mechanical strength of the sintered product.

[0003] Polyacetal (POM) is known as one of the organic compounds that make up the binder (e.g., organic binder) used in this powder injection molding method. POM has the advantages of increasing the strength of green bodies, suppressing deformation during debinding, and leaving no residue after sintering.

[0004] On the other hand, POM has poor compatibility with organic compounds such as polyethylene, which is added to maintain the shape of the molded body during debinding, and paraffin wax, which is added to maintain good injection moldability. In order to obtain a homogeneous feedstock, the amount of POM added had to be reduced, and the effect of POM was therefore limited.

[0005] Therefore, Japanese Patent Application Laid-Open No. 2001-106581 discloses the use of a polyolefin modified with methacrylic acid or the like as an organic binder for the purpose of improving compatibility with POM.

[0006] In addition, JP2009-542880A proposes an organic binder consisting of POM, polyethylene, and poly-1,3-dioxepane. Conventionally, POM and polyethylene have low compatibility, but by blending poly-1,3-dioxepane, an organic binder with good dispersibility is obtained.

[0007] On the other hand, in order to improve compatibility with other organic compounds while maintaining the properties of POM, it is effective to use modified polyacetal resins in which other molecular structures such as polyolefins are introduced into the molecular chain of POM. International Publication No. 2001 / 009213 has proposed a block copolymer consisting of a polyoxymethylene chain and a hydrogenated polybutadiene. Japanese Patent Application Publication No. 09-111306 proposes the use of a polyolefin-based polymer modified polyacetal resin as a binder composed of an organic compound, and proposes a composition for producing a sintered molded body that uses the polyolefin-based polymer modified polyacetal resin as a binder and is easily mixed with a polyolefin resin. Furthermore JP 2004-076153 A It has also been proposed to use modified polyacetal as a binder composed of an organic compound.

[0008] In addition, the POM-containing binders used in powder injection molding have the disadvantage that they decompose when exposed to heat during the kneading process with sinterable inorganic powder and the injection molding process.

[0009] In order to maintain the advantages of POM while suppressing decomposition during the kneading and injection molding processes, it is effective to use modified polyacetal resins in which other molecular structures, such as polyolefins, are introduced into the molecular chains of POM. As such a POM, WO 2001 / 009213 proposes a block copolymer consisting of a polyoxymethylene chain and a hydrogenated polybutadiene. In addition, JP-A-09-111306 proposes the use of a polyolefin-based polymer modified polyacetal resin as a binder composed of an organic compound. It is described that the use of the polyolefin-based polymer modified polyacetal resin as a binder in powder injection molding has high thermal decomposition performance in the debinding step and is less likely to cause deformation when heated. Furthermore, Japanese Patent Application Laid-Open No. 2004-076153 also proposes the use of modified polyacetal as a binder composed of an organic compound. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] JP 2001-106581 A [Patent Document 2] Special Publication No. 2009-542880 [Patent Document 3] International Publication No. 2001 / 009213 [Patent Document 4] Japanese Patent Application Publication No. 09-111306 [Patent Document 5] JP 2004-076153 A Summary of the Invention [Problem to be solved by the invention]

[0011] An object of the present invention is to provide a composition containing a modified polyacetal that is suitable for inorganic powder injection molding applications.

[0012] Regarding the invention (I), the method described in JP-A-2001-106581 requires a long time for melt-kneading with POM and other resin components, and the effect of improving dispersibility with POM is limited. In addition, in the method described in JP 2009-542880 A, although the incorporation of poly-1,3-dioxepane certainly improves dispersibility, it is necessary to incorporate a polyolefin from the viewpoint of shape retention during degreasing, and it takes time to melt both the POM and the polyolefin, and the effect of improving dispersibility is also limited. Furthermore, in the method described in WO 2001 / 009213, when a polyacetal segment is (A) and a hydrogenated polybutadiene segment is (B), an (A)-(B)-(A) block copolymer is formed, which is excellent in improving compatibility with polyolefins and inorganic fillers; however, the incorporation of the sinterable inorganic powder described in the present application was not anticipated. Furthermore, the methods disclosed in JP-A-09-111306 and JP-A-2004-076153 contain resins such as polyolefin in addition to the modified polyacetal, which results in problems such as a long melt-kneading time and variations in dispersibility between lots.

[0013] Therefore, an object of the invention (I) is to obtain a composition for inorganic powder injection molding, which contains a modified polyacetal and can shorten the kneading time and has excellent injection moldability.

[0014] Regarding invention (II), the method described in JP 2001-514017 A aims to form a large-diameter gear having high circularity, excellent dimensional stability and durability, and did not anticipate the incorporation of sinterable inorganic powder. In addition, in the method described in JP-A-09-111306, although the structure of the polyolefin to be introduced is clear, the structure of the POM, which is the main structure of the modified polyacetal, is unclear, resulting in a problem of insufficient decomposition suppression effect. Furthermore, in the method described in JP-A-2004-076153, although modified polyacetal is described, no specific structure is mentioned, and there is a problem that the decomposition suppression effect is insufficient.

[0015] Therefore, an object of the invention (II) is to obtain a composition for inorganic powder injection molding containing a modified polyacetal, which does not impair the shape retention of green molded bodies based on the rigidity of the polyacetal resin, and which is inhibited from decomposing during the process of kneading with inorganic powder and injection molding. [Means for solving the problem]

[0016] The gist of the inventions (I) and (II) is as follows.

[0017] With regard to invention (I), the present inventors conducted intensive research to solve the above-mentioned problems, and as a result, discovered that the above-mentioned problems can be solved by a composition for inorganic powder injection molding, which contains a sinterable inorganic powder and an organic binder including a modified polyacetal (C) having a polyacetal segment (A) and a modified segment (B) with a number average molecular weight in a specific range, and having a melt flow rate of 70 g / 10 min or more and 160 g / 10 min or less at 190°C and 2.16 kg, and thus arrived at invention (I).

[0018] That is, the invention (I) is as follows. [Invention (I)] [1] a sinterable inorganic powder; An organic binder including a modified polyacetal (C) having a polyacetal segment (A) and a modified segment (B); An inorganic powder injection molding composition comprising: The modified polyacetal (C) has a melt flow rate (MFR) of 70 g / 10 min or more and 160 g / 10 min or less, measured under conditions of 190° C. and 2.16 kg; The modified segment (B) has a number average molecular weight of 500 to 10,000. 1. A composition for inorganic powder injection molding comprising: [2] The inorganic powder injection molding composition according to [1], wherein the modified segment (B) is a polyolefin. [3] The composition for inorganic powder injection molding according to [1] or [2], wherein the modified segment (B) is a hydrogenated polybutadiene. [4] The composition for inorganic powder injection molding according to any one of [1] to [3], wherein the modified polyacetal (C) has a number average molecular weight of 10,000 to 50,000. [5] The composition for inorganic powder injection molding according to any one of [1] to [4], wherein the polyacetal segment (A) comprises 95.0 to 99.9 mol % of oxymethylene units and 0.1 to 5.0 mol % of oxyalkylene units represented by formula (1). [ka] (In the formula, each R is independently selected from a hydrogen atom, an alkyl group, a substituted alkyl group, an aryl group, and a substituted aryl group, and m is an integer selected from 2 to 6.) [6] The composition for inorganic powder injection molding according to any one of [1] to [5], wherein the modified polyacetal (C) is a block copolymer represented by (A)-(B)-(A). [7] The composition for inorganic powder injection molding according to any one of [1] to [6], further comprising a lubricant. [8] An injection molded article comprising the inorganic powder injection molding composition according to any one of [1] to [7]. [9] [8] A sintered body obtained by debinding and sintering the injection molded body described in [8].

[0019] With regard to invention (II), the present inventors conducted intensive research to solve the above-mentioned problems, and as a result, discovered that the above-mentioned problems can be solved by a composition for inorganic powder injection molding, which includes an organic binder containing a modified polyacetal in which the number average molecular weight of the modified polyacetal, the number average molecular weight of the modified portion, and the molar ratio of oxymethylene units and oxyalkylene units constituting the polyacetal segment have been adjusted, and thus arrived at invention (II).

[0020] That is, the invention (II) is as follows. [Invention (II)] [1] a sinterable inorganic powder; An organic binder including a modified polyacetal (C) having a polyacetal segment (A) and a modified segment (B); An inorganic powder injection molding composition comprising: The modified polyacetal (C) has a number average molecular weight of 10,000 to 500,000; The modified segment (B) has a number average molecular weight of 500 to 10,000; The polyacetal segment (A) is composed of 95.0 to 99.9 mol % of oxymethylene units and 0.1 to 5.0 mol % of oxyalkylene units represented by formula (1), 1. A composition for inorganic powder injection molding comprising: [ka] (In the formula, each R is independently selected from the group consisting of a hydrogen atom, an alkyl group, a substituted alkyl group, an aryl group, and a substituted aryl group, and m is an integer selected from 2 to 6.) [2] The composition for inorganic powder injection molding according to [1], wherein a ratio (Mn2 / Mn1×100(%)) of the number average molecular weight (Mn2) of the modified segment (B) to the number average molecular weight (Mn1) of the modified polyacetal (C) is 0.5% or more and 10% or less. [3] The composition for inorganic powder injection molding according to [1] or [2], wherein the modified segment (B) is a polyolefin. [4] The composition for inorganic powder injection molding according to any one of [1] to [3], wherein the modified segment (B) is a hydrogenated polybutadiene. [5] The composition for inorganic powder injection molding according to any one of [1] to [4], wherein the modified polyacetal (C) is a block copolymer represented by (A)-(B)-(A). [6] The composition for inorganic powder injection molding according to any one of [1] to [5], wherein a polyacetal molecular weight reduction rate of the weight average molecular weight of the modified polyacetal extracted after treating the composition for inorganic powder injection molding in chloroform under conditions of 80° C. for 8 hours relative to the weight average molecular weight of the modified polyacetal (C) is 40% or less. [7] The composition for inorganic powder injection molding according to any one of [1] to [6], comprising a polyolefin resin having a melt flow rate (MFR) of 60 g / 10 min or more measured under conditions of 230° C. and 2.16 kg. [8] An injection molded article comprising the inorganic powder injection molding composition according to any one of [1] to [7]. [9] [8] A sintered body obtained by debinding and sintering the injection molded body described in [8]. Effect of the Invention

[0021] According to the present invention, it is possible to provide a composition containing a modified polyacetal suitable for inorganic powder injection molding applications.

[0022] In particular, according to invention (I), a homogeneous composition for inorganic powder injection molding can be obtained in a short melt-kneading time. Moreover, by using the composition for inorganic powder injection molding of invention (I), it is possible to obtain a sintered body with a good yield because it has excellent injection moldability and does not cause cracks or bulges during the debinding and sintering processes. In particular, it is preferable that the kneading time can be shortened and the injection moldability is excellent even if the amount of resin components other than the polyacetal resin in the composition for inorganic powder injection molding is small (preferably not included).

[0023] In addition, according to the invention (II), it is possible to obtain a composition for inorganic powder injection molding containing a modified polyacetal, which does not impair the shape retention of a green molded body based on the rigidity of the polyacetal resin, and in which decomposition is suppressed during the process of kneading with an inorganic powder or during injection molding. Furthermore, by using the inorganic powder injection molding composition of invention (II), it is possible to obtain sintered bodies with good yields because it has excellent injection moldability and does not cause cracks or blistering during the debinding and sintering processes. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] Hereinafter, the embodiments of the present invention will be described in detail. Note that the present invention is not limited to the following description, and can be modified in various ways within the scope of the present invention.

[0025] The inorganic powder injection molding composition of the present embodiment is a composition for inorganic powder injection molding that contains a sinterable inorganic powder and an organic binder that contains a modified polyacetal (C) having a polyacetal segment (A) and a modified segment (B), and the modified segment (B) has a number average molecular weight of 500 to 10000. The inorganic powder injection molding composition of the present embodiment can be used for inorganic powder injection applications. Preferred embodiments of the inorganic powder injection molding composition of this embodiment include the following invention (I) and invention (II).

[0026] The invention (I) will now be described. [Invention (I)] [Inorganic powder injection molding composition] The inorganic powder injection molding composition of the present embodiment contains a sinterable inorganic powder and an organic binder containing a modified polyacetal (C) consisting of a polyacetal segment (A) and a modified segment (B). The inorganic powder injection molding composition of the present embodiment may further contain other additives in addition to the sinterable inorganic powder and the organic binder, or may be a composition consisting of only the inorganic powder and the organic binder. The inorganic powder injection molding composition of this embodiment preferably contains only the modified polyacetal (C), the unreacted polyacetal described below, the polyamide resin as a nitrogen-containing compound described below, and the resin as a lubricant, and preferably does not contain polyolefin resins or the like that are usually blended to maintain the shape of a molded body during degreasing. The mass ratio of aggregate resins other than the polyacetal resin (the modified polyacetal (C), the unreacted polyacetal described below, and the like) blended to maintain the shape of a molded body during degreasing in 100 parts by mass of the inorganic powder injection molding composition of this embodiment may be 1 part by mass or less, 0.5 parts by mass or less, or 0.01 parts by mass or less.

[0027] <Sinterable inorganic powder> The inorganic powder can be selected from any of the known suitable sinterable inorganic powders, preferably metal powders, alloy powders, metal carbonyl powders, ceramic powders and mixtures thereof, with metal powders and ceramic powders being particularly preferred in order to provide functionality. The sinterable inorganic powder may be used alone or in combination of two or more kinds. The sinterable inorganic powder may be an inorganic powder having a melting point between 500°C and 2000°C and an average particle size of 100 μm or less. The melting point can be determined from the endothermic peak top by heating at 5°C / min under an argon gas flow using a differential scanning calorimeter. The average particle size means the average diameter at 50% cumulative weight measured using a particle size distribution measuring device that employs a laser diffraction scattering method. The meanings of these terms are the same hereinafter unless otherwise specified.

[0028] Specific examples of the metal powder include powders of aluminum, magnesium, barium, calcium, cobalt, zinc, copper, nickel, iron, silicon, titanium, tungsten, and metal compounds and metal alloys based on these metals, whereby not only already completed alloys but also mixtures of the individual alloy components can be used.

[0029] Examples of the ceramic powder include oxides such as zinc oxide, aluminum oxide, and zirconia; hydroxides such as hydroxyapatite; carbides such as silicon carbide; nitrides such as silicon nitride and boron nitride; halides such as fluorite; silicates such as stearite; titanates such as barium titanate and lead zirconate titanate; carbonates; phosphates; ferrite; and the like.

[0030] The inorganic powders described above may be used alone, or may be used in combination with several inorganic substances such as various metal powders, metal alloys, and ceramic powders. In view of being particularly excellent in kneadability and injection moldability when used together with an organic binder containing modified polyacetal (C), preferred metal powders and alloy powders include titanium alloys and stainless steels such as SUS316L, and preferred ceramic powders include aluminum oxide and zirconia.

[0031] The average particle size of the inorganic powder is preferably 30 μm or less, and more preferably 20 μm or less.

[0032] The mass ratio of the sinterable inorganic powder is preferably 70 to 95 mass%, more preferably 75 to 95 mass%, and particularly preferably 80 to 95 mass%, relative to 100 mass% of the inorganic powder injection molding composition. By having the sinterable inorganic powder within the above range, a composition for sintered molded bodies having excellent kneadability and a melt viscosity suitable for injection molding can be obtained, and a green molded body with high strength can be obtained.

[0033] <Organic binder> The organic binder preferably contains a modified polyacetal (C) consisting of a polyacetal segment (A) and a modified segment (B), and further contains a lubricant. Since the modified polyacetal resin has a modified segment consisting of a polyacetal segment and a polyolefin in its molecule, it has good adhesion to sinterable inorganic powder even if the amount of aggregate resin other than the modified polyacetal (C) blended to maintain the shape of the molded body during degreasing is small (preferably without blending other aggregate resin), and also exhibits good shape retention during the degreasing process. The organic binder preferably contains a modified polyacetal mixture containing modified polyacetal (C) described below. The organic binder may further contain a lubricant, an aggregate resin other than polyacetal, and an additive, or may be a mixture consisting of a modified polyacetal mixture or a lubricant alone. The resin component containing an oxymethylene unit contained in the organic binder is preferably only modified polyacetal (C) described below.

[0034] (Modified polyacetal mixture) The modified polyacetal mixture contains the modified polyacetal (C) and may further contain a nitrogen-containing compound and a fatty acid metal salt. Among them, it is preferable that the modified polyacetal mixture contains the modified polyacetal (C) and the only optional components are a nitrogen-containing compound and a fatty acid metal salt.

[0035] -Modified polyacetal (C)- The organic binder includes a modified polyacetal (C) from the viewpoints of kneading with a sinterable inorganic powder and thermal stability during the injection molding process. In general, modified polyacetal is a block copolymer having a polyacetal segment and a modified segment. The polyacetal segment may be a homopolymer residue consisting of only oxymethylene units, or a copolymer residue in which oxymethylene units and oxyalkylene units are randomly copolymerized. The modified segment is a component that does not fall under the category of a polyacetal segment, and examples thereof include polyolefin, polyurethane, polyester, polyamide, polystyrene, and polyalkyl acrylate. The modified polyacetal (C) in this embodiment has a polyacetal segment (A) and a modified segment (B), and may be composed of only the polyacetal segment (A) and the modified segment (B). As described later, the polyacetal segment (A) is a polyacetal copolymer residue in which oxymethylene units and oxyalkylene units are randomly copolymerized, and the modified segment (B) is preferably a polyolefin or polyurethane. The modified polyacetal (C) may be used alone or in combination of two or more kinds.

[0036] From the viewpoint of obtaining green molded bodies in a good yield in an injection molding process, the number average molecular weight of the modified polyacetal (C) is preferably 10,000 to 500,000, more preferably 10,000 to 50,000, and even more preferably 10,000 to 20,000. From the viewpoint of molding small, thin parts, the number average molecular weight is preferably 20,000 to 200,000, and more preferably 20,000 to 100,000. The number average molecular weight of the modified polyacetal (C) can be measured by GPC. Specific conditions for GPC include, for example, a GPC device HLC-8120 manufactured by Tosoh Corporation, a column HFIP806 (two 30 cm columns) manufactured by Showa Denko K.K., a carrier hexafluoroisopropanol (hereinafter referred to as HFIP), and a standard sample polymethyl methacrylate (PMMA) manufactured by Polymer Laboratory Co., Ltd., at a temperature of 40°C and a flow rate of 0.5 ml / min.

[0037] The number average molecular weight of the modified segment (B) constituting the modified polyacetal (C) is preferably 500 to 10,000 (polystyrene equivalent) from the viewpoint of obtaining a green molded body with good yield in an injection molding process, and more preferably 2,000 to 5,000 (polystyrene equivalent) from the viewpoint of suppressing decomposition of the modified polyacetal (C) during kneading with a sinterable inorganic powder. The molecular weight distribution (Mw / Mn) of the modified segment (B) is preferably less than 2. The number average molecular weight of the modified segment (B) can be measured using GPC. For example, the number average molecular weight can be measured using a Waters 150C GPC device, 1,2,4-trichlorobenzene as a carrier, and polystyrene as a standard sample at a temperature of 140°C. If the number average molecular weight of the modified segment (B) is to be measured for any modified polyacetal resin produced by a third party, it is preferable to decompose the polyacetal block in advance before measurement.

[0038] The ratio (Mn2 / Mn1×100(%)) of the number average molecular weight (Mn2) of the modified segment (B) to the number average molecular weight (Mn1) of the modified polyacetal (C) is preferably 0.5% or more and 10% or less from the viewpoint of preventing cracking and swelling of the molded body in the debinding and sintering steps, and more preferably 0.5% or more and 5.0% or less from the viewpoint of improving the yield in the injection molding step.

[0039] The modified segment (B) of the modified polyacetal (C) can suitably be a polyolefin or a polyurethane. From the viewpoint of reducing the residue derived from the organic binder in the degreasing step, a polyolefin is preferred. Specific examples include polyethylene, polypropylene, ethylene-propylene copolymer, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, polyisoprene, polybutadiene, and hydrogenated polybutadiene. Polyethylene, polypropylene, and hydrogenated polybutadiene are preferred, and hydrogenated polybutadiene is more preferred from the viewpoint of shape retention in the degreasing step and suppression of cracking and swelling in the degreasing step. The modified polyacetal (C) may contain one or more types of modified segment (B), and from the viewpoint of ease of production, it is preferable that the modified polyacetal (C) contains one type of modified segment (B).

[0040] The polyacetal segment (A) of the modified polyacetal (C) is composed of a polyacetal copolymer residue containing an oxymethylene unit (i.e., (CHO) unit) resulting from ring-opening polymerization of trioxane, and an oxyalkylene unit (sometimes simply referred to as an "oxyalkylene unit" in this specification) represented by the following formula (1) resulting from ring-opening polymerization of a cyclic formal (or a cyclic ether). The polyacetal segment (A) is preferably composed of only the oxymethylene unit and the oxyalkylene unit. In addition, it is preferable that the oxymethylene unit and the oxyalkylene unit are present randomly in the polyacetal segment (A), i.e., the polyacetal copolymer residue. [ka] (In the formula, each R is independently selected from a hydrogen atom, an alkyl group, a substituted alkyl group, an aryl group, and a substituted aryl group, and m is an integer selected from 2 to 6.) The oxyalkylene unit represented by the formula (1) contained in the polyacetal segment (A) may be of one type or of multiple types, and is preferably of one type from the viewpoint of ease of production.

[0041] From the viewpoint of suppressing thermal decomposition of the modified polyacetal (C) during the kneading step with the sinterable inorganic powder, the polyacetal segment (A) preferably comprises 95.0 to 99.9 mol % of oxymethylene units and 0.1 to 5.0 mol % of oxyalkylene units, and more preferably 98.0 to 99.7 mol % of oxymethylene units and 0.3 to 2.0 mol % of oxyalkylene units. The mole percentage of the monomer units constituting the polyacetal segment (A) can be measured by the following method. The modified polyacetal and 1N hydrochloric acid are placed in a pressure bottle and heated at 130°C for 2 hours to hydrolyze the modified polyacetal and obtain an alkylene glycol component resulting from the cyclic formal (or cyclic ether). After the hydrolysis, hydroxyalkylated modified segments are also present, but these hydroxyalkylated modified segments are present as a phase separation from the aqueous solution. Meanwhile, the alkylene glycol components present in the aqueous solution after the hydrolysis are quantified by gas chromatography.

[0042] Specific examples of the oxyalkylene unit represented by the above formula (1) derived from a cyclic formal (or a cyclic ether) include an ethylene oxide residue, a propylene oxide residue, a 1,3-dioxolane residue, a 1,3,5-trioxepane residue, a diethylene glycol formal residue, a 1,4-butanediol formal residue, a 1,3-dioxane residue, etc. Among them, from the viewpoint of the production rate of the modified polyacetal (C), the oxyalkylene unit is preferably a 1,3-dioxolane residue, a 1,3,5-trioxepane residue, or a 1,4-butanediol formal residue, and more preferably a 1,3-dioxolane residue. In particular, it is preferable to convert a 1,3-dioxolane residue obtained by polymerizing 1,3-dioxolane having 500 ppm by mass or less of 2-methyl-1,3-dioxolane and 15 ppm by mass or less of peroxide calculated as hydrogen peroxide into an oxyalkylene unit, and further to add 10 to 500 ppm by mass of one or more types of hindered phenols during polymerization. The content of 2-methyl-1,3-dioxolane can be measured by a hydrogen flame ion detector using a gas chromatograph equipped with a Gas Chlopack 55 manufactured by GL Sciences, Inc. Specifically, the peroxide content in 1,3-dioxolane is calculated by adding 40 ml of isopropyl alcohol, 10 ml of saturated sodium iodide solution (NaI dissolved in isopropyl alcohol), 2 ml of acetic acid, and 25 g of 1,3-dioxolane to a flask, refluxing at 100°C for about 5 minutes, and immediately thereafter titrating with 0.01N sodium thiosulfate until the color of the mixture in the flask changes from yellow to colorless, determining the titer (represented as A ml), and using this as a blank titration, the same procedure is performed without using 1,3-dioxolane to obtain the titer (represented as B ml), and then calculating the peroxide content by the following formula. Amount of peroxide (converted to hydrogen peroxide, ppm) = (AB) x 17 x 0.01 / (25 x 1000) x 106

[0043] From the viewpoint of suppressing decomposition of the modified polyacetal (C) during the kneading process with a sinterable inorganic powder, the modified polyacetal (C) is preferably a block copolymer represented by polyacetal segment (A)-modified segment (B)-polyacetal segment (A) (sometimes referred to herein as (A)-(B)-(A), ABA, etc.) or modified segment (B)-polyacetal segment (A)-modified segment (B) (sometimes referred to herein as (B)-(A)-(B), BAB, etc.). Furthermore, from the viewpoint of strength expression of a green molded body, it is more preferably (A)-(B)-(A). Whether or not any polyacetal resin is a block copolymer can be identified using known methods. For example, a method can be considered in which polyacetal resins with known structures are used as target samples and the amount of formaldehyde generated during resin decomposition is quantitatively compared.

[0044] The melt flow rate of the modified polyacetal (C) measured according to ASTM-D-1238-57T under conditions of 190°C and 2.16 kg is 70g / 10min or more, preferably 70g / 10min to 160g / 10min, more preferably 90g / 10min to 160g / 10min, and even more preferably 90g / 10min to 150g / 10min. When the melt flow rate is 70g / 10min or more, the flowability of the inorganic powder injection molding composition is improved, and the injection moldability is excellent even in a small and thin shape. When the melt flow rate is 160g / 10min or less, the strength of the green molded body is improved.

[0045] The mass proportion of the modified polyacetal (C) in 100% by mass of the modified polyacetal mixture is preferably 95% by mass or more, more preferably 97% by mass or more and less than 100% by mass, and even more preferably 97 to 99.9% by mass.

[0046] The mass proportion of the modified polyacetal (C) in 100 mass% of the organic binder is preferably 1 to 40 mass%, more preferably 1 to 20 mass%, and particularly preferably 1 to 10 mass%, from the viewpoint of reducing decomposition products of the polyacetal during the kneading and injection molding processes.

[0047] The mass proportion of the modified polyacetal (C) in 100 mass% of the inorganic powder injection molding composition is preferably 1 to 20 mass%, more preferably 2 to 15 mass%, and even more preferably 4 to 10 mass%, from the viewpoint of excellent shape retention of a green molded body containing an inorganic powder.

[0048] The ratio of the mass of the inorganic powder to the mass of the modified polyacetal (C) in the inorganic powder injection molding composition (mass of inorganic powder / mass of modified polyacetal (C)) is preferably 5 to 200, more preferably 10 to 100, and even more preferably 15 to 50, from the viewpoints of the shape retention of the green molded body and preventing cracking and swelling of the molded body during the debinding and sintering steps.

[0049] The method for producing the modified polyacetal (C) is not particularly limited, and the modified polyacetal (C) can be obtained by a known method. Depending on the method for producing the modified polyacetal (C), the reaction product of the modified polyacetal may be coexisted with an unreacted polyacetal resin and / or an unreacted polyolefin polymer, and may be in the form of a substantially compatible or uniformly dispersed mixture. The unreacted polyacetal resin and the unreacted polyolefin polymer generated by the method for producing the modified polyacetal (C) may be the above-mentioned thermoplastic resin, which is one component of the composition for inorganic powder injection molding.

[0050] -Nitrogen-containing compounds, fatty acid metal salts- The modified polyacetal mixture preferably further contains a nitrogen-containing compound and / or a fatty acid metal salt, and more preferably contains a nitrogen-containing compound and a fatty acid metal salt. By including the nitrogen-containing compound and the fatty acid metal salt, the extrudability, thermal stability, and suppression of foreign matter during the production of a modified polyacetal mixture can be improved. In addition, the flowability of the inorganic powder injection molding composition kneaded with the metal powder and the strength of the green molded body tend to be improved at the same time. By including the nitrogen-containing compound and the fatty acid metal salt, the inorganic powder injection molding composition has improved thermal stability.

[0051] The nitrogen-containing compound is not particularly limited, but examples thereof include polyamide resins, amide compounds, urea derivatives, triazine derivatives, etc., and among them, polyamide resins are preferred from the viewpoint of providing a composition for inorganic powder injection molding with better thermal stability and a green molded body with better strength. These compounds may be used alone or in combination of two or more.

[0052] Examples of the polyamide resin include, but are not limited to, nylon 6, nylon 11, nylon 12, nylon 66, nylon 6·10, nylon 6 / 6·10, nylon 6 / 6·6, nylon 6·6 / 6·10, nylon 6 / 6·6 / 6·10, poly-β-alanine, and the like, which are obtained by condensation of diamines and dicarboxylic acids, condensation of amino acids, ring-opening polymerization of lactams, etc.

[0053] Examples of the amide compound include, but are not limited to, stearyl stearamide, stearyl oleamide, stearyl erucamide, ethylenediamine-distearate amide, ethylenediamine-dibehenate amide, hexamethylenediamine-distearate amide, ethylenediamine-dierucate amide, xylylenediamine-dierucate amide, di(xylylenediamine-stearate amide), and sebacate amide, which are produced from an aliphatic monocarboxylic acid, an aliphatic dicarboxylic acid, an aromatic monocarboxylic acid, or an aromatic dicarboxylic acid and an aliphatic monoamine, an aliphatic diamine, an aromatic monoamine, or an aromatic diamine.

[0054] The urea derivative is not particularly limited, but examples thereof include N-phenylurea, N,N'-diphenylurea, N-phenylthiourea, and N,N'-diphenylthiourea.

[0055] The triazine derivative is not particularly limited, but examples thereof include melamine, benzoguanamine, N-phenylmelamine, melem, N,N'-diphenylmelamine, N-methylolmelamine, N,N'-trimethylolmelamine, 2,4-diamino-6-cyclohexyltriazine, and melam.

[0056] The mass ratio of the nitrogen-containing compound is preferably 0.005 to 0.2 parts by mass, and particularly preferably 0.005 to 0.1 parts by mass, relative to 100 parts by mass of the modified polyacetal mixture. The mass ratio of the nitrogen-containing compound within the above range is preferable from the viewpoint of improving the thermal stability of the modified polyacetal mixture when kneading the sinterable inorganic powder and the organic binder.

[0057] The fatty acid metal salt is not particularly limited, but examples thereof include fatty acid metal salts obtained from a saturated or unsaturated fatty acid having 10 to 35 carbon atoms or a fatty acid substituted with a hydroxyl group and an alkali metal or alkaline earth metal hydroxide, oxide, or chloride. These may be used alone or in combination of two or more.

[0058] Examples of the fatty acid of the fatty acid metal salt include capric acid, undecylic acid, lauric acid, tridecylic acid, myristic acid, pentadecylic acid, palmitic acid, heptadecylic acid, stearic acid, nonadecanoic acid, arachic acid, behenic acid, liglyceric acid, cerotic acid, heptacosanoic acid, montanic acid, undecylenic acid, oleic acid, elaidic acid, cetoleic acid, erucic acid, brassidic acid, sorbic acid, linoleic acid, linolenic acid, arachidonic acid, propiolic acid, stearic acid, 12-hydroxydodecanoic acid, 3-hydroxydecanoic acid, 16-hydroxyhexadecanoic acid, 10-hydroxyhexadecanoic acid, 12-hydroxyoctadecanoic acid, and 10-hydroxy-8-octadecanoic acid. The metal compound is a hydroxide or chloride of an alkali metal such as lithium, sodium, or potassium, an alkaline earth metal such as magnesium, calcium, strontium, or barium, or zinc or aluminum. Of these, the fatty acid is preferably myristic acid, palmitic acid, or stearic acid, and the metal compound is preferably a hydroxide, oxide, or chloride of calcium, and more preferably calcium myristate, calcium palmitate, or calcium stearate.

[0059] When the nitrogen-containing compound and the fatty acid metal salt are added to the modified polyacetal mixture, it is preferable that the ratio of the mass of the fatty acid metal salt to the mass of the nitrogen-containing compound (mass of fatty acid metal salt / mass of nitrogen-containing compound) is in a specific range, specifically, the ratio is 1 to 15, preferably 1 to 10. By setting the ratio to 1 to 15, it is possible to improve the thermal stability of the modified polyacetal mixture (for example, the modified polyacetal (C)) in the organic binder, which is preferable.

[0060] (Aggregate resin other than polyacetal) The organic binder may further contain aggregate resin other than polyacetal. Here, aggregate resin refers to a thermoplastic resin that is blended to maintain the strength of the molded body and to maintain the shape of the molded body during degreasing. Examples of aggregate resin other than polyacetal include polyolefin resin and the above-mentioned nitrogen-containing compound which is a resin. Note that the lubricant described later is not included in aggregate resin other than polyacetal.

[0061] -Polyolefin resin- The organic binder may further contain a polyolefin resin. The polyolefin resin is preferably a homopolymer or copolymer having a structural unit derived from an alkene having 2 to 8 carbon atoms, preferably 2 to 4 carbon atoms.

[0062] From the viewpoints of kneadability with sinterable inorganic powders and injection moldability, the polyolefin resin preferably has a melt flow index measured under conditions of 230°C and 2.16 kg of 40 g / 10 min or more, and more preferably 60 g / 10 min or more.

[0063] Specific examples of the polyolefin resin include polyethylene, polypropylene, ethylene-propylene copolymer, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, polyisoprene, polybutadiene, etc. Polyethylene, polypropylene, and mixtures thereof are preferred, and polyethylene or polypropylene is more preferred from the viewpoint of shape retention in the degreasing step and suppression of cracking and swelling in the degreasing step. Suitable examples of commercially available polyethylene include Santech HD series, Santech LD series, Santech EVA series (all manufactured by Asahi Kasei), Neozex, Ultzex, and Evolu (all manufactured by Prime Polymer), and examples of polypropylene include Sumitomo Noblen (manufactured by Sumitomo Chemical), Novatec PP (manufactured by Japan Polypropylene), Sanallomer PM series (manufactured by Sanallomer), and Prime Polypro (manufactured by Prime Polymer).

[0064] From the viewpoint of shape retention of a molded product after acid degreasing, the polyolefin resin is preferably not easily decomposed by acid. From the viewpoint of shape retention of a molded product after acid degreasing, the weight of the polyolefin resin after immersion in a 30% aqueous nitric acid solution at 23°C (room temperature) and 70°C for 24 hours according to the method described in JIS K 7114 is preferably 10% or less, more preferably 5% or less, and particularly preferably 1% or less, of the weight before immersion.

[0065] From the viewpoint of further reducing cracks and blistering during the degreasing step, the difference between the thermal decomposition onset point (°C) of the modified polyacetal (C) and the thermal decomposition onset point (°C) of the polyolefin resin is preferably 30°C or more, more preferably 30 to 100°C. The thermal decomposition onset point is a temperature measured using a thermogravimetric differential thermal analyzer.

[0066] The addition of polyolefin resin to the organic binder is optional, and the mass ratio of the polyolefin resin may be selected within a range that does not affect the shape retention of the green molded body and the shape of the molded body after acid degreasing. The mass ratio of the polyolefin resin in the organic binder is preferably 2 mass% or less, more preferably 1 mass% or less, and particularly preferably 0.5 mass% or less, based on 100 mass% of the organic binder, from the viewpoint of being able to maintain the shape of the green molded body and the shape of the molded body after acid degreasing well.

[0067] (Polyacetal) The organic binder may further contain polyacetal. The polyacetal may be an unreacted polyacetal generated in the production of the modified polyacetal (C) described above. The polyacetal may be one represented by the following formula (3): The polyacetal may be one type or a plurality of types. [ka] (In the formula, R1 and R2 are independently selected from the group consisting of hydrogen, an alkyl group, a substituted alkyl group, an aryl group, and a substituted aryl group, p=95 to 100 mol %, q=0 to 5 mol %, p+q=100 mol %, and z is an integer selected from 2 to 6.)

[0068] (lubricant) The organic binder preferably further contains a lubricant, which further improves the flowability of the inorganic powder injection molding composition, enabling good injection molding of even fine molded products.

[0069] The lubricant is a compound other than the polyacetal resin and polyolefin resin, and examples of the waxes include, for example, paraffin wax, polyethylene wax, polypropylene wax, carnauba wax, polyethylene glycol, polytetramethylene ether glycol, polytetraethylene glycol, polyisobutylene, microcrystalline wax, montan wax, beeswax, Japan wax, synthetic wax, poly-1,3-dioxolane, poly-1,3-dioxepane, etc. Among them, paraffin wax, polyethylene glycol, polytetramethylene ether glycol, and poly-1,3-dioxepane are preferred from the viewpoint of further improving the fluidity of the inorganic powder injection molding composition in injection molding.

[0070] From the viewpoint of achieving even better fluidity of the inorganic powder injection molding composition during injection molding, the mass proportion of the lubricant is preferably 5 to 60 mass %, more preferably 5 to 50 mass %, and particularly preferably 10 to 50 mass %, relative to 100 mass % of the organic binder.

[0071] The mass proportion of the organic binder in 100 mass% of the inorganic powder injection molding composition of this embodiment is preferably 5 to 30 mass%, more preferably 5 to 20 mass%, and even more preferably 5 to 10 mass%.

[0072] <Other additives> Additives other than the above-mentioned components that can be added to the inorganic powder injection molding composition are not limited as long as they do not impair the effects of the present invention. Preferred additives include antioxidants. Examples of the antioxidant include n-octadecyl-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate, n-octadecyl-3-(3'-methyl-5'-t-butyl-4'-hydroxyphenyl)propionate, n-tetradecyl-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate, 1,6-hexanediol-bis-(3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate), 1,4-butanediol-bis-(3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate), 3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, triethylene glycol-bis-(3-(3-t-butyl-5-methyl-4-hydroxyphenyl)propionate), tetradecyl-3-(3',5'-di-t-butyl-4-hydroxyphenyl)propionate, ... Examples of the hydroxyphenyl ether include trachys(methylene 3-(3'-t-butyl-4-hydroxyphenyl)propionate)methane, N,N'-bis-(3-(3,5-di-t-butyl-4-hydroxyphenol)propionyl)hydrazine, N,N'-tetramethylene-bis-3-(3'-methyl-5'-t-butyl-4-hydroxyphenol)propionyldiamine, N,N'-bis-3-(3',5'-di-t-butyl-4-hydroxyphenol)propionylhexamethylenediamine, 3-(N-salicyloyl)amino-1,2,4-triazole, N,N'-bis-(2-(3-(3,5-dibutyl-4-hydroxyphenyl)propionyloxy)ethyl)oxyamide, and N,N'-hexamethylene-bis-(3-3,5-t-butyl-4-hydroxyphenyl)propanamide. These antioxidants may be used alone or in combination of two or more. The content of the antioxidant is 0.01 to 1.0 mass %, preferably 0.05 to 0.5 mass %, based on 100 mass % of the modified polyacetal (C). When the content is within the above range, the thermal stability is improved.

[0073] The inorganic powder injection molding composition of this embodiment can be produced, for example, by mixing the above-mentioned inorganic powder, the above-mentioned organic binder, and the above-mentioned additives.

[0074] The inorganic powder injection molding composition of the present embodiment can be used as a raw material for a sintered body. The sintered body may be a sintered body obtained by injection molding the inorganic powder injection molding composition to obtain an injection molded body containing the inorganic powder injection molding composition, and degreasing and sintering the injection molded body. Examples of the sintered body include automobile parts, aircraft parts, medical device parts, electric and electronic device parts, and defense device parts.

[0075] The invention (II) is as follows. [Invention (II)] [Inorganic powder injection molding composition] The inorganic powder injection molding composition of the present embodiment contains a sinterable inorganic powder and an organic binder containing a modified polyacetal (C) consisting of a polyacetal segment (A) and a modified segment (B). The inorganic powder injection molding composition of the present embodiment may further contain other additives in addition to the sinterable inorganic powder and the organic binder, or may be a composition consisting of only the inorganic powder and the organic binder.

[0076] <Sinterable inorganic powder> The inorganic powder can be selected from any of the known suitable sinterable inorganic powders, preferably metal powders, alloy powders, metal carbonyl powders, ceramic powders and mixtures thereof, with metal powders and ceramic powders being particularly preferred in order to provide functionality. The above sinterable inorganic powders may be used alone or in combination of two or more kinds. The sinterable inorganic powder may be an inorganic powder having a melting point between 500°C and 2000°C and an average particle size of 100 μm or less. The melting point can be determined from the endothermic peak top by heating at 5°C / min under an argon gas flow using a differential scanning calorimeter. The average particle size means the average diameter at 50% cumulative weight measured using a particle size distribution measuring device that employs a laser diffraction scattering method. The meanings of these terms are the same hereinafter unless otherwise specified.

[0077] Specific examples of the metal powder include powders of aluminum, magnesium, barium, calcium, cobalt, zinc, copper, nickel, iron, silicon, titanium, tungsten, and metal compounds and metal alloys based on these metals, whereby not only already completed alloys but also mixtures of the individual alloy components can be used.

[0078] Examples of the ceramic powder include oxides such as zinc oxide, aluminum oxide, and zirconia, hydroxides such as hydroxyapatite, carbides such as silicon carbide, nitrides such as silicon nitride and boron nitride, halides such as fluorite, silicates such as stearite, titanates such as barium titanate and lead zirconate titanate, carbonates, phosphates, ferrite, and the like.

[0079] The inorganic powders described above may be used alone, or may be used in combination with several inorganic substances such as various metal powders, metal powders, and ceramic powders. From the viewpoint of being particularly excellent in shape retention of the green molded body and suppression of decomposition during kneading and injection molding when used together with an organic binder containing modified polyacetal (C), preferred metal powders and alloy powders include titanium alloys and stainless steels such as SUS316L, and preferred ceramic powders include aluminum oxide and zirconia.

[0080] The average particle size of the inorganic powder is preferably 30 μm or less, and more preferably 20 μm or less.

[0081] The mass ratio of the sinterable inorganic powder is preferably 70 to 95 mass%, more preferably 75 to 95 mass%, and particularly preferably 80 to 95 mass%, relative to 100 mass% of the inorganic powder injection molding composition. By having the sinterable inorganic powder within the above range, a composition for sintered molded bodies having a melt viscosity suitable for injection molding can be obtained, and a green molded body with high strength can be obtained.

[0082] <Organic binder> The organic binder contains a modified polyacetal (C) consisting of a polyacetal segment (A) and a modified segment (B). The organic binder preferably contains a modified polyacetal mixture containing the modified polyacetal (C) described below. The organic binder may further contain an optional thermoplastic resin or additive, or may be a mixture consisting of only the modified polyacetal mixture, the polyolefin resin, and the fluidity imparting agent. The resin component containing an oxymethylene unit contained in the organic binder is preferably only the modified polyacetal (C) described below.

[0083] (Modified polyacetal mixture) The modified polyacetal mixture contains the modified polyacetal (C) and may further contain a nitrogen-containing compound and a fatty acid metal salt. Among them, it is preferable that the modified polyacetal mixture contains the modified polyacetal (C) and the only optional components are a nitrogen-containing compound and a fatty acid metal salt.

[0084] -Modified polyacetal (C)- The organic binder includes a modified polyacetal (C) from the viewpoints of kneading with a sinterable inorganic powder and thermal stability during the injection molding process. In general, modified polyacetal is a block copolymer having a polyacetal segment and a modified segment. The polyacetal segment may be a homopolymer residue consisting of only oxymethylene units, or a copolymer residue in which oxymethylene units and oxyalkylene units are randomly copolymerized. The modified segment is a component that does not fall under the category of a polyacetal segment, and examples thereof include polyolefin, polyurethane, polyester, polyamide, polystyrene, and polyalkyl acrylate. The modified polyacetal (C) in this embodiment has a polyacetal segment (A) and a modified segment (B), and may be composed of only the polyacetal segment (A) and the modified segment (B). As described later, the polyacetal segment (A) is a polyacetal copolymer residue in which oxymethylene units and oxyalkylene units are randomly copolymerized, and the modified segment (B) is preferably a polyolefin or polyurethane. The modified polyacetal (C) may be used alone or in combination of two or more kinds.

[0085] The number average molecular weight of the modified polyacetal (C) is preferably 10,000 to 500,000 from the viewpoint of obtaining green molded bodies with good yield in the injection molding step, and is more preferably 20,000 to 200,000, and more preferably 20,000 to 100,000 from the viewpoint of molding small, thin parts. The number average molecular weight of the modified polyacetal (C) can be measured by GPC. Specific conditions for GPC include, for example, a GPC device HLC-8120 manufactured by Tosoh Corporation, a column HFIP806 (two 30 cm columns) manufactured by Showa Denko K.K., a carrier hexafluoroisopropanol (hereinafter referred to as HFIP), and a standard sample polymethyl methacrylate (PMMA) manufactured by Polymer Laboratory Co., Ltd., at a temperature of 40°C and a flow rate of 0.5 ml / min.

[0086] The number average molecular weight of the modified segment (B) constituting the modified polyacetal (C) is preferably 500 to 10,000 (polystyrene equivalent) from the viewpoint of obtaining a green molded body with good yield in an injection molding process, and more preferably 2,000 to 5,000 (polystyrene equivalent) from the viewpoint of suppressing decomposition of the modified polyacetal (C) during kneading with a sinterable inorganic powder. The molecular weight distribution (Mw / Mn) of the modified segment (B) is preferably less than 2. The number average molecular weight of the modified segment (B) can be measured using GPC. For example, the number average molecular weight can be measured using a Waters 150C GPC device, 1,2,4-trichlorobenzene as a carrier, and polystyrene as a standard sample at a temperature of 140°C. If the number average molecular weight of the modified segment (B) is to be measured for any modified polyacetal resin produced by a third party, it is preferable to decompose the polyacetal block in advance before measurement.

[0087] The ratio (Mn2 / Mn1×100(%)) of the number average molecular weight (Mn2) of the modified segment (B) to the number average molecular weight (Mn1) of the modified polyacetal (C) is preferably 0.5% or more and 10% or less from the viewpoint of preventing cracking and swelling of the molded body in the debinding and sintering steps, and more preferably 0.5% or more and 5.0% or less from the viewpoint of improving the yield in the injection molding step.

[0088] The modified segment (B) of the modified polyacetal (C) can suitably be a polyolefin or a polyurethane. From the viewpoint of reducing the residue derived from the organic binder in the degreasing step, a polyolefin is preferred. Specific examples include polyethylene, polypropylene, ethylene-propylene copolymer, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, polyisoprene, polybutadiene, and hydrogenated polybutadiene. Polyethylene, polypropylene, and hydrogenated polybutadiene are preferred, and hydrogenated polybutadiene is more preferred from the viewpoint of shape retention in the degreasing step and suppression of cracking and swelling in the degreasing step. The modified polyacetal (C) may contain one or more types of modified segment (B), and from the viewpoint of ease of production, it is preferable that the modified polyacetal (C) contains one type of modified segment (B).

[0089] The polyacetal segment (A) of the modified polyacetal (C) is composed of a polyacetal copolymer residue containing an oxymethylene unit (i.e., (CHO) unit) resulting from ring-opening polymerization of trioxane, and an oxyalkylene unit (sometimes simply referred to as an "oxyalkylene unit" in this specification) represented by the following formula (1) resulting from ring-opening polymerization of a cyclic formal (or a cyclic ether). The polyacetal segment (A) is preferably composed of only the oxymethylene unit and the oxyalkylene unit. In addition, it is preferable that the oxymethylene unit and the oxyalkylene unit are present randomly in the polyacetal segment (A), i.e., the polyacetal copolymer residue. [ka] (In the formula, each R is independently selected from a hydrogen atom, an alkyl group, a substituted alkyl group, an aryl group, and a substituted aryl group, and m is an integer selected from 2 to 6.) The oxyalkylene unit represented by the formula (1) contained in the polyacetal segment (A) may be of one type or of multiple types, and is preferably of one type from the viewpoint of ease of production.

[0090] The polyacetal segment (A) is composed of 95.0 to 99.9 mol % oxymethylene units and 0.1 to 5.0 mol % oxyalkylene units, preferably 98.0 to 99.7 mol % oxymethylene units and 0.3 to 2.0 mol % oxyalkylene units, from the viewpoint of suppressing thermal decomposition of the modified polyacetal (C) during the kneading process with the sinterable inorganic powder. The mole percentage of the monomer units constituting the polyacetal segment (A) can be measured by the following method. The modified polyacetal and 1N hydrochloric acid are placed in a pressure bottle and heated at 130°C for 2 hours to hydrolyze the modified polyacetal and obtain an alkylene glycol component resulting from the cyclic formal (or cyclic ether). After the hydrolysis, hydroxyalkylated modified segments are also present, but these hydroxyalkylated modified segments are present as a phase separation from the aqueous solution. Meanwhile, the alkylene glycol components present in the aqueous solution after the hydrolysis are quantified by gas chromatography.

[0091] Specific examples of the oxyalkylene unit represented by the above formula (1) derived from a cyclic formal (or a cyclic ether) include an ethylene oxide residue, a propylene oxide residue, a 1,3-dioxolane residue, a 1,3,5-trioxepane residue, a diethylene glycol formal residue, a 1,4-butanediol formal residue, a 1,3-dioxane residue, etc. Among them, from the viewpoint of the production rate of the modified polyacetal (C), the oxyalkylene unit is preferably a 1,3-dioxolane residue, a 1,3,5-trioxepane residue, or a 1,4-butanediol formal residue, and more preferably a 1,3-dioxolane residue. In particular, it is preferable to convert a 1,3-dioxolane residue obtained by polymerizing 1,3-dioxolane having 500 ppm by mass or less of 2-methyl-1,3-dioxolane and 15 ppm by mass or less of peroxide calculated as hydrogen peroxide into an oxyalkylene unit, and further to add 10 to 500 ppm by mass of one or more types of hindered phenols during polymerization. The content of 2-methyl-1,3-dioxolane can be measured by a hydrogen flame ion detector using a gas chromatograph equipped with a Gas Chlopack 55 manufactured by GL Sciences, Inc. Specifically, the peroxide content in 1,3-dioxolane is calculated by adding 40 ml of isopropyl alcohol, 10 ml of saturated sodium iodide solution (NaI dissolved in isopropyl alcohol), 2 ml of acetic acid, and 25 g of 1,3-dioxolane to a flask, refluxing at 100°C for about 5 minutes, and immediately thereafter titrating with 0.01N sodium thiosulfate until the color of the mixture in the flask changes from yellow to colorless, determining the titer (represented as A ml), and using this as a blank titration, the same procedure is performed without using 1,3-dioxolane, but the titer (represented as B ml) is calculated by the following formula. Amount of peroxide (converted to hydrogen peroxide, ppm) = (AB) x 17 x 0.01 / (25 x 1000) x 106

[0092] From the viewpoint of suppressing decomposition of the modified polyacetal (C) during the kneading process with a sinterable inorganic powder, the modified polyacetal (C) is preferably a block copolymer represented by polyacetal segment (A)-modified segment (B)-polyacetal segment (A) (sometimes referred to herein as (A)-(B)-(A), ABA, etc.) or modified segment (B)-polyacetal segment (A)-modified segment (B) (sometimes referred to herein as (B)-(A)-(B), BAB, etc.). Furthermore, from the viewpoint of strength expression of a green molded body, it is more preferably (A)-(B)-(A). Whether or not any polyacetal resin is a block copolymer can be identified using known methods. For example, a method can be considered in which polyacetal resins with known structures are used as target samples and the amount of formaldehyde generated during resin decomposition is quantitatively compared.

[0093] The modified polyacetal (C) is not easily decomposed even when subjected to a process in which heat is applied, such as kneading with a sinterable inorganic powder or injection molding, so that the desired composition for inorganic powder injection molding and injection molded article can be obtained. When the weight average molecular weight of the modified polyacetal (C) in the composition for inorganic powder injection molding is Mw1 and the weight average molecular weight of the modified polyacetal extracted from the composition for inorganic powder injection molding under conditions of 80°C in chloroform for 8 hours is Mw2, the polyacetal molecular weight reduction rate represented by the following formula is preferably 40% or less from the viewpoint of maintaining good injection moldability, more preferably 20% or less from the viewpoint of maintaining the strength of the molded article, and more preferably 10% or less from the viewpoint of reducing odor in the workplace. Polyacetal molecular weight reduction rate (%) = (1-Mw2 / Mw1) x 100 The extraction conditions may be the conditions described in "1. Evaluation of thermal stability of polyacetal" in the Examples section below.

[0094] The mass proportion of the modified polyacetal (C) in 100% by mass of the modified polyacetal mixture is preferably 95% by mass or more, more preferably 97% by mass or more and less than 100% by mass, and even more preferably 97 to 99.9% by mass.

[0095] The mass proportion of the modified polyacetal (C) in 100 mass% of the organic binder is preferably 1 to 40 mass%, more preferably 1 to 20 mass%, and particularly preferably 1 to 10 mass%, from the viewpoint of reducing decomposition products of the polyacetal during the kneading and injection molding processes.

[0096] The mass proportion of the modified polyacetal (C) in 100 mass% of the inorganic powder injection molding composition is preferably 1 to 20 mass%, more preferably 2 to 15 mass%, and even more preferably 4 to 10 mass%, from the viewpoint of excellent shape retention of a green molded body containing an inorganic powder.

[0097] The ratio of the mass of the inorganic powder to the mass of the modified polyacetal (C) in the inorganic powder injection molding composition (mass of inorganic powder / mass of modified polyacetal (C)) is preferably 5 to 200, more preferably 10 to 100, and even more preferably 15 to 50, from the viewpoints of the shape retention of the green molded body and preventing cracking and swelling of the molded body during the debinding and sintering steps.

[0098] The method for producing the modified polyacetal (C) is not particularly limited, and the modified polyacetal (C) can be obtained by a known method. Depending on the method for producing the modified polyacetal (C), the reaction product of the modified polyacetal may be coexisted with an unreacted polyacetal resin and / or an unreacted polyolefin polymer, and may be in the form of a substantially compatible or uniformly dispersed mixture. The unreacted polyacetal resin and the unreacted polyolefin polymer generated by the method for producing the modified polyacetal (C) may be the above-mentioned thermoplastic resin, which is one component of the composition for inorganic powder injection molding.

[0099] -Nitrogen-containing compounds, fatty acid metal salts- The modified polyacetal mixture preferably further contains a nitrogen-containing compound and / or a fatty acid metal salt, and more preferably contains a nitrogen-containing compound and a fatty acid metal salt. By including the nitrogen-containing compound and the fatty acid metal salt, the extrudability, thermal stability, and suppression of foreign matter during the production of a modified polyacetal mixture can be improved. In addition, the flowability of the inorganic powder injection molding composition kneaded with the metal powder and the strength of the green molded body tend to be improved at the same time. By including the nitrogen-containing compound and the fatty acid metal salt, the inorganic powder injection molding composition has improved thermal stability.

[0100] The nitrogen-containing compound is not particularly limited, but examples thereof include polyamide resins, amide compounds, urea derivatives, triazine derivatives, etc., and among them, polyamide resins are preferred from the viewpoint of providing a composition for inorganic powder injection molding with better thermal stability and a green molded body with better strength. These compounds may be used alone or in combination of two or more.

[0101] Examples of the polyamide resin include, but are not limited to, nylon 6, nylon 11, nylon 12, nylon 66, nylon 6·10, nylon 6 / 6·10, nylon 6 / 6·6, nylon 6·6 / 6·10, nylon 6 / 6·6 / 6·10, poly-β-alanine, and the like, which are obtained by condensation of diamines and dicarboxylic acids, condensation of amino acids, ring-opening polymerization of lactams, etc.

[0102] Examples of the amide compound include, but are not limited to, stearyl stearamide, stearyl oleamide, stearyl erucamide, ethylenediamine-distearate amide, ethylenediamine-dibehenate amide, hexamethylenediamine-distearate amide, ethylenediamine-dierucate amide, xylylenediamine-dierucate amide, di(xylylenediamine-stearate amide), and sebacate amide, which are produced from an aliphatic monocarboxylic acid, an aliphatic dicarboxylic acid, an aromatic monocarboxylic acid, or an aromatic dicarboxylic acid and an aliphatic monoamine, an aliphatic diamine, an aromatic monoamine, or an aromatic diamine.

[0103] The urea derivative is not particularly limited, but examples thereof include N-phenylurea, N,N'-diphenylurea, N-phenylthiourea, and N,N'-diphenylthiourea.

[0104] The triazine derivative is not particularly limited, but examples thereof include melamine, benzoguanamine, N-phenylmelamine, melem, N,N'-diphenylmelamine, N-methylolmelamine, N,N'-trimethylolmelamine, 2,4-diamino-6-cyclohexyltriazine, and melam.

[0105] The mass ratio of the nitrogen-containing compound is preferably 0.005 to 0.2 parts by mass, and particularly preferably 0.005 to 0.1 parts by mass, relative to 100 parts by mass of the modified polyacetal mixture. The mass ratio of the nitrogen-containing compound within the above range is preferable from the viewpoint of improving the thermal stability of the modified polyacetal mixture when kneading the sinterable inorganic powder and the organic binder.

[0106] The fatty acid metal salt is not particularly limited, but examples thereof include fatty acid metal salts obtained from a saturated or unsaturated fatty acid having 10 to 35 carbon atoms or a fatty acid substituted with a hydroxyl group and an alkali metal or alkaline earth metal hydroxide, oxide, or chloride. These may be used alone or in combination of two or more.

[0107] Examples of the fatty acid of the fatty acid metal salt include capric acid, undecylic acid, lauric acid, tridecylic acid, myristic acid, pentadecylic acid, palmitic acid, heptadecylic acid, stearic acid, nonadecanoic acid, arachic acid, behenic acid, liglyceric acid, cerotic acid, heptacosanoic acid, montanic acid, undecylenic acid, oleic acid, elaidic acid, cetoleic acid, erucic acid, brassidic acid, sorbic acid, linoleic acid, linolenic acid, arachidonic acid, propiolic acid, stearic acid, 12-hydroxydodecanoic acid, 3-hydroxydecanoic acid, 16-hydroxyhexadecanoic acid, 10-hydroxyhexadecanoic acid, 12-hydroxyoctadecanoic acid, and 10-hydroxy-8-octadecanoic acid. The metal compound is a hydroxide or chloride of an alkali metal such as lithium, sodium, or potassium, an alkaline earth metal such as magnesium, calcium, strontium, or barium, or zinc or aluminum. Of these, the fatty acid is preferably myristic acid, palmitic acid, or stearic acid, and the metal compound is preferably a hydroxide, oxide, or chloride of calcium, and more preferably calcium myristate, calcium palmitate, or calcium stearate.

[0108] When the nitrogen-containing compound and the fatty acid metal salt are added to the modified polyacetal mixture, it is preferable that the ratio of the mass of the fatty acid metal salt to the mass of the nitrogen-containing compound (mass of fatty acid metal salt / mass of nitrogen-containing compound) is in a specific range, specifically, the ratio is 1 to 15, preferably 1 to 10. By setting the ratio to 1 to 15, it is possible to improve the thermal stability of the modified polyacetal mixture (for example, the modified polyacetal (C)) in the organic binder, which is preferable.

[0109] (thermoplastic resin) The organic binder may further contain a thermoplastic resin, such as a polyacetal resin or a polyolefin resin.

[0110] -Polyolefin resin- The organic binder may further contain a polyolefin resin. The polyolefin resin is preferably a homopolymer or copolymer having a structural unit derived from an alkene having 2 to 8 carbon atoms, preferably 2 to 4 carbon atoms.

[0111] From the viewpoints of kneadability with sinterable inorganic powders and injection moldability, the polyolefin resin preferably has a melt flow index measured under conditions of 230°C and 2.16 kg of 40 g / 10 min or more, and more preferably 60 g / 10 min or more.

[0112] Specific examples of the polyolefin resin include polyethylene, polypropylene, ethylene-propylene copolymer, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, polyisoprene, polybutadiene, etc. Polyethylene, polypropylene, and mixtures thereof are preferred, and polyethylene or polypropylene is more preferred from the viewpoint of shape retention in the degreasing step and suppression of cracking and swelling in the degreasing step. Suitable examples of commercially available polyethylene include Santech HD series, Santech LD series, Santech EVA series (all manufactured by Asahi Kasei), Neozex, Ultzex, and Evolu (all manufactured by Prime Polymer), and examples of polypropylene include Sumitomo Noblen (manufactured by Sumitomo Chemical), Novatec PP (manufactured by Japan Polypropylene), Sanallomer PM series (manufactured by Sanallomer), and Prime Polypro (manufactured by Prime Polymer).

[0113] From the viewpoint of shape retention of a molded product after acid degreasing, the polyolefin resin is preferably not easily decomposed by acid. From the viewpoint of shape retention of a molded product after acid degreasing, the weight of the polyolefin resin after immersion in a 30% aqueous nitric acid solution at 23°C (room temperature) and 70°C for 24 hours according to the method described in JIS K 7114 is preferably 10% or less, more preferably 5% or less, and particularly preferably 1% or less, of the weight before immersion.

[0114] From the viewpoint of further reducing cracks and blistering during the degreasing step, the difference between the thermal decomposition onset point (°C) of the modified polyacetal (C) and the thermal decomposition onset point (°C) of the polyolefin resin is preferably 30°C or more, more preferably 30 to 100°C. The thermal decomposition onset point is a temperature measured using a thermogravimetric differential thermal analyzer.

[0115] From the viewpoint of maintaining the shape of the green molded body and maintaining the shape of the molded body after acid degreasing well, the mass proportion of the polyolefin resin in the organic binder is preferably 5 to 95 mass%, more preferably 5 to 70 mass%, and particularly preferably 5 to 60 mass%, relative to 100 mass% of the organic binder.

[0116] The mass proportion of the polyolefin resin relative to 100% by mass of the polyacetal resin is preferably from 1 to 200% by mass, more preferably from 5 to 150% by mass, and further preferably from 10 to 120% by mass. The total mass ratio of the polyacetal resin and the polyolefin resin in 100% by mass of the organic binder is preferably 45% by mass or more, and more preferably 90% by mass or more. In addition, the total mass ratio of the polyacetal resin, the polyolefin resin, and the fluidity imparting agent described below in 100% by mass of the organic binder is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 98% by mass or more.

[0117] -Polyacetal- The polyacetal may be an unreacted polyacetal generated in the production of the modified polyacetal (C) described above. The polyacetal may be one represented by the following formula (3): The polyacetal may be one type or a plurality of types. [ka] (In the formula, R1 and R2 are independently selected from the group consisting of hydrogen, an alkyl group, a substituted alkyl group, an aryl group, and a substituted aryl group, p=95 to 100 mol %, q=0 to 5 mol %, p+q=100 mol %, and z is an integer selected from 2 to 6.)

[0118] (Fluidity imparting agent) The organic binder preferably further contains a fluidity imparting agent, which further improves the fluidity of the inorganic powder injection molding composition, thereby enabling good injection molding of even fine molded products.

[0119] The above-mentioned fluidity imparting agent is a compound other than the above-mentioned polyacetal resin and polyolefin resin, and examples thereof include waxes. Examples of the above-mentioned waxes include paraffin wax, polyethylene wax, polypropylene wax, carnauba wax, polyethylene glycol, polytetramethylene ether glycol, polytetraethylene glycol, polyisobutylene, microcrystalline wax, montan wax, beeswax, Japan wax, synthetic wax, poly-1,3-dioxolane, poly-1,3-dioxepane, etc. Among them, paraffin wax, polyethylene glycol, polytetramethylene ether glycol, and poly-1,3-dioxepane are preferred from the viewpoint of further improving the fluidity of the inorganic powder injection molding composition in injection molding.

[0120] From the viewpoint of achieving even better fluidity of the inorganic powder injection molding composition during injection molding, the mass proportion of the fluidity imparting agent is preferably 5 to 60 mass %, more preferably 5 to 50 mass %, and particularly preferably 10 to 50 mass %, relative to 100 mass % of the organic binder.

[0121] The mass proportion of the organic binder in 100 mass% of the inorganic powder injection molding composition of this embodiment is preferably 5 to 30 mass%, more preferably 5 to 20 mass%, and even more preferably 5 to 10 mass%.

[0122] <Other additives> Additives other than the above-mentioned components that can be added to the inorganic powder injection molding composition are not limited as long as they do not impair the effects of the present invention. Preferred additives include antioxidants. Examples of the antioxidant include n-octadecyl-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate, n-octadecyl-3-(3'-methyl-5'-t-butyl-4'-hydroxyphenyl)propionate, n-tetradecyl-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate, 1,6-hexanediol-bis-(3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate), 1,4-butanediol-bis-(3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate), 3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, triethylene glycol-bis-(3-(3-t-butyl-5-methyl-4-hydroxyphenyl)propionate), tetradecyl-3-(3',5'-di-t-butyl-4-hydroxyphenyl)propionate, ... Examples of the hydroxyphenyl ether include trachys(methylene 3-(3'-t-butyl-4-hydroxyphenyl)propionate)methane, N,N'-bis-(3-(3,5-di-t-butyl-4-hydroxyphenol)propionyl)hydrazine, N,N'-tetramethylene-bis-3-(3'-methyl-5'-t-butyl-4-hydroxyphenol)propionyldiamine, N,N'-bis-3-(3',5'-di-t-butyl-4-hydroxyphenol)propionylhexamethylenediamine, 3-(N-salicyloyl)amino-1,2,4-triazole, N,N'-bis-(2-(3-(3,5-dibutyl-4-hydroxyphenyl)propionyloxy)ethyl)oxyamide, and N,N'-hexamethylene-bis-(3-3,5-t-butyl-4-hydroxyphenyl)propanamide. These antioxidants may be used alone or in combination of two or more. The content of the antioxidant is 0.01 to 1.0 mass %, preferably 0.05 to 0.5 mass %, based on 100 mass % of the modified polyacetal (C). When the content is within the above range, the thermal stability is improved.

[0123] The polyacetal molecular weight reduction rate of the weight average molecular weight of the modified polyacetal obtained by extracting the inorganic powder injection molding composition in chloroform at 80° C. for 8 hours relative to the weight average molecular weight of the modified polyacetal (C) is 40% or less, preferably 5 to 36%, and more preferably 7 to 26%. The polyacetal molecular weight reduction rate can be measured by the method described later in the Examples.

[0124] The inorganic powder injection molding composition of this embodiment can be produced by mixing the above-mentioned inorganic powder, the above-mentioned organic binder, and the above-mentioned additives.

[0125] The inorganic powder injection molding composition of the present embodiment can be used as a raw material for a sintered body. The sintered body may be a sintered body obtained by injection molding the inorganic powder injection molding composition to obtain an injection molded body containing the inorganic powder injection molding composition, and degreasing and sintering the injection molded body. Examples of the sintered body include automobile parts, aircraft parts, medical device parts, electric and electronic device parts, and defense device parts. EXAMPLES

[0126] The present invention will be described in detail below with reference to specific examples and comparative examples, but the present invention is not limited to the following examples.

[0127] [Examples of the Invention (I)] The terms and measurement methods for properties in the examples and comparative examples are as follows.

[0128] [Production of modified polyacetal (C)] Hydrogenated polybutadiene 1 with hydroxyalkylated ends, represented by the following formulas (4) and (5), hydrogenated polybutadiene 2, and hydrogenated polybutadiene 3 with hydroxyalkylated end, represented by the following formula (6), were used as chain transfer agents, and polymerization was performed by the method described in Japanese Patent No. 4560261 to obtain modified polyacetals I-1 to I-13 in which the polyacetal segments were composed of oxymethylene units and oxyethylene units. For comparison, unmodified polyacetal I-1 using methanol as the chain transfer agent was also polymerized. The number average molecular weights (Mn1) of the obtained modified polyacetals and unmodified polyacetals (C), the number average molecular weights (Mn2) of the modified segments, the molar ratio of the oxyethylene units in the polyacetal segments (A), and the melt flow rate (MFR) of the modified polyacetal (C) are shown in Table 1. [ka] (In the formula, l, m, and n each represent an integer of 1 to 50.) [ka] (In the formula, x and y each represent an integer of 1 to 50.) [ka] (In the formula, o, p, and q each represent an integer of 1 to 50.) The melt flow rate was measured in accordance with ASTM-D-1238-57T under conditions of 190° C. and 2.16 kg.

[0129] [Production of polyacetal composition] 0.05 parts by mass of nylon 66 and 0.3 parts by mass of calcium stearate were uniformly added and mixed with 100 parts by mass of the modified polyacetal (C), and the mixture was fed to a vented twin-screw extruder (L / D=40) set at 200°C, and pelletized while degassing under reduced pressure at 90 kPa. The mixture was then dried at 100°C for 2 hours to obtain modified polyacetal mixtures I-1 to I-13. Moreover, additives were similarly blended except that 100 parts by mass of unmodified polyacetal was used instead of the modified polyacetal, to obtain an unmodified polyacetal mixture I-1.

[0130] [Production of sinterable inorganic powder injection molding composition] 1) Preparation of sinterable inorganic powder injection molding compositions for acid degreasing The modified polyacetal mixtures I-1 to I-13, polytetramethylene ether glycol (PTMG3000, Mitsubishi Chemical Corporation) as a lubricant, and SUS316L (DAP316L, Daido Steel Co., Ltd.) as a sinterable inorganic powder were mixed in the mass ratios shown in Table 2 in an MS-type pressure kneader (DS3-10, Nippon Spindle Mfg. Co., Ltd.) heated to 170°C, and kneaded for 30 minutes. The obtained kneaded products were fed into a Wheeley type pulverizer (manufactured by Yoshida Seisakusho) and pulverized to obtain sinterable inorganic powder injection molding compositions I-1 to I-13 for acid degreasing. Also, instead of using the modified polyacetal mixture, the unmodified polyacetal mixture I-1 was used, and low-density polyethylene (Suntec™ LDPE M6555, manufactured by Asahi Kasei Corporation), polytetramethylene ether glycol, and SUS316L were mixed in the ratios shown in Table 2 and kneaded for 30 minutes. The resulting kneaded product was fed into a Wiley-type pulverizer (manufactured by Yoshida Seisakusho) and pulverized to obtain a sinterable inorganic powder injection molding composition for acid degreasing.

[0131] 2) Preparation of sinterable inorganic powder injection molding composition for thermal debinding The above modified polyacetal mixtures I-1 to I-13, paraffin wax (Paraffin wax-145, Nippon Seiro Co., Ltd.) as a lubricant, and SUS316L (DAP316L, Daido Steel Co., Ltd.) as a sinterable inorganic powder were mixed in the proportions shown in Table 3 in an MS-type pressure kneader (DS3-10 model, Nippon Spindle Mfg. Co., Ltd.) heated to 170°C, and kneaded for 30 minutes. The resulting kneaded product was fed into a Wheeley type pulverizer (manufactured by Yoshida Seisakusho) and pulverized to obtain a sinterable inorganic powder injection molding composition for thermal degreasing. Also, instead of using the modified polyacetal mixture, unmodified polyacetal mixture I-1, polypropylene (Sumitomo Noblen U501E1, manufactured by Sumitomo Chemical Co., Ltd.) having an MFR of 230°C and 2.16 kg at 120 g / 10 min, paraffin wax, and SUS316L were mixed in the ratios shown in Table 3 and kneaded for 30 minutes to obtain a sinterable inorganic powder injection molding composition for thermal degreasing.

[0132] [evaluation] 1.Injection moldability Using an injection molding machine (ROBOSHOT α-50iA manufactured by Fanuc), molding was performed at a molding temperature of 175 to 200°C to obtain dumbbell-shaped green molded specimens conforming to ISO 10724-1. The molded bodies were visually observed for deformation, and were judged as good if no deformation was observed, poor if deformation was observed, and unmoldable if injection molding was not possible. The results are shown in Tables 2 and 3.

[0133] 2. Shape retention of degreased compacts 2-1: Shape retention after acid degreasing In Examples I-1 to I-7 and Comparative Examples I-1 to I-8, acid degreasing was carried out. The compact was supported at two points with a 50 mm interval and set in a degreasing furnace. The furnace was first heated to 110°C and replaced with nitrogen gas at 500 l / h for 30 minutes. Then, 30 ml / h of 98% nitric acid was fed while maintaining nitrogen purging. The nitric acid feed was maintained for 2.5 hours, followed by replacing the furnace with nitrogen gas at 500 l / h for 45 minutes and cooling to room temperature for degreasing. The appearance of the obtained degreased molded body was visually observed, and those without distortion or damage were judged as good, and those with distortion or damage were judged as bad. Note that those that could not be injection molded were not tested. The results are shown in Table 2. 2-2: Shape retention after heat degreasing For Examples I-8 to I-14 and Comparative Examples I-9 to I-16, thermal degreasing was performed. The above molded body was supported at two points with an interval of 50 mm and set in a degreasing furnace. Next, the inside of the degreasing furnace was purged with nitrogen gas, and the temperature was raised to 500°C at a rate of 30°C / hr as the first condition and a rate of 45°C / hr as the second condition, and degreasing was performed by holding at 500°C for 2 hours. The appearance of the degreasing molded body was visually observed, and those without distortion or damage were judged as good, and those with distortion or damage were judged as bad. Incidentally, those that could not be injection molded were not subjected to the experiment. The results are shown in Table 3.

[0134] 3: Observation of the shape of sintered bodies After degreasing under each condition, sintering was carried out for Examples I-1 to I-14 and Comparative Examples I-1 to I-16. The degreased green body was transferred to a sintering furnace, and the inside of the furnace was replaced with argon gas, after which the temperature was raised from room temperature to 600°C at a rate of 5°C / min. After holding at 600°C for 1 hour, the temperature was raised to 1350°C at a rate of 5°C / min under reduced pressure of 1 to 5 Torr, and held for 1 hour to perform sintering, and then cooled to room temperature. The shape of the obtained sintered body was visually observed, and those that did not show cracks or bulges were rated as good, and those that did show cracks or bulges were rated as bad. Those that could not be injection molded were rated as not being molded. The results are shown in Tables 2 and 3.

[0135] 4: Density measurement For samples that were visually free of cracks and blisters, they were left to stand for 24 hours at room temperature of 23°C and humidity of 50% RH, and then their weights were measured. The samples were then left to stand in water for 24 hours, and their weights were measured in water. The samples were then removed from the water, the moisture was wiped off, and their weights were measured. The density was calculated using these weights, and the density of the SUS316L used (7.8 g / cm 3 The ratio (%) of the total number of samples was calculated. The results are shown in Tables 2 and 3.

[0136] [Table 1]

[0137] [Table 2]

[0138] [Table 3]

[0139] [Example of Invention (II)] The terms and measurement methods for properties in the examples and comparative examples are as follows.

[0140] [Production of modified polyacetal II-1] A jacketed twin-shaft paddle type continuous polymerizer capable of passing a heat medium was adjusted to 80° C., and the following raw materials (1) to (3) and catalyst (4) were continuously fed to carry out polymerization. (1) Trioxane: 133 mol / hr (2) 1,3-dioxolane: 3.5 mol / hour (3) Hydrogenated polybutadiene having hydroxylated ends and represented by the following formula (4) having a number average molecular weight of 2390: 0.1 mol / hour [ka] (In the formula, l, m, and n indicate the ratio of each unit and do not indicate the bonding state. l, m, and n are each an integer of 1 to 50.) (4) Catalyst (boron trifluoride di-n-butyl ether dissolved in cyclohexane): 5 × 10 per mole of trioxane -5 Mole The block copolymer discharged from the polymerization machine was poured into a 1% aqueous solution of triethylamine to completely deactivate the polymerization catalyst. The block copolymer was filtered, washed with acetone, and then dried in a vacuum dryer set at 60°C (hereinafter, this polymerization method is abbreviated as "polymerization method 1"). Next, 100 parts by mass of the block copolymer was contacted with 2 parts by mass of water as a terminal stabilizing agent and 1 part by mass of triethylamine as a basic substance, and melt-kneaded to hydrolyze and stabilize the hydroxyoxymethylene chain, which is an unstable terminal chain. In terminal stabilization, the block copolymer was first fed to a vented twin-screw extruder set at 200°C and melt-kneaded. Next, water / triethylamine was continuously fed before extrusion and kneaded with the block copolymer. Subsequently, formaldehyde, water, and triethylamine were removed, and terminal stabilization treatment of the block copolymer was performed (hereinafter, sometimes referred to as terminal stabilization treatment 1). The degree of vacuum during the terminal stabilization treatment was set to 4 kPa, and degassing was performed. The block copolymer obtained from the die of the extruder was extruded as a strand and pelletized. This resulted in the production of modified polyacetal II-1. The number average molecular weight (Mn1) of the obtained modified polyacetal II-1, the number average molecular weight (Mn2) of the modified segment, the ratio of the number average molecular weight (Mn2) of the modified segment (B) to the number average molecular weight (Mn1) of the modified polyacetal (Mn2 / Mn1×100(%)), and the ratio of oxyethylene units in the polyacetal segment (A) are shown in Table 4.

[0141] [Production of modified polyacetals II-2, II-3, II-6, II-9, II-10, II-13, and II-14] Block copolymers were polymerized in the same manner as in polymerization method 1, except that the feed rates per hour of trioxane, 1,3-dioxolane, and polybutadiene with both terminal hydroxyl groups represented by formula (4) to the twin-screw paddle-type continuous polymerization reactor were variously changed, and the terminals of the block copolymers were stabilized in the same manner as in terminal stabilization treatment 1, to obtain modified polyacetals II-2, II-3, II-6, II-9, II-10, II-13, and II-14. The number average molecular weight (Mn1) of the obtained modified polyacetal, the number average molecular weight (Mn2) of the modified segment, the ratio of the number average molecular weight (Mn2) of the modified segment (B) to the number average molecular weight (Mn1) of the modified polyacetal (Mn2 / Mn1×100(%)), and the ratio of oxyethylene units in the polyacetal segment (A) are shown in Table 4.

[0142] [Production of modified polyacetal II-4] Modified polyacetal II-4 was obtained by carrying out polymerization and terminal stabilization in the same manner as for modified polyacetal II-1, except that a polybutadiene having hydroxyl groups at both ends and represented by formula (4) and having a number average molecular weight of 1,376 was used. The number average molecular weight (Mn1) of the obtained modified polyacetal II-4, the number average molecular weight (Mn2) of the modified segment, the ratio of the number average molecular weight (Mn2) of the modified segment (B) to the number average molecular weight (Mn1) of the modified polyacetal (Mn2 / Mn1×100(%)), and the ratio of oxyethylene units in the polyacetal segment (A) are shown in Table 4.

[0143] [Production of Modified Polyacetal II-5] Modified polyacetal II-5 was obtained by carrying out polymerization and terminal stabilization in the same manner as in modified polyacetal II-1, except that a polybutadiene having hydroxyl groups at both ends and represented by formula (4) and having a number average molecular weight of 9,384 was used. The number average molecular weight (Mn1) of the obtained modified polyacetal II-5, the number average molecular weight (Mn2) of the modified segment, the ratio of the number average molecular weight (Mn2) of the modified segment (B) to the number average molecular weight (Mn1) of the modified polyacetal (Mn2 / Mn1×100(%)), and the ratio of oxyethylene units in the polyacetal segment (A) are shown in Table 4.

[0144] [Production of Modified Polyacetal II-7] A block copolymer was polymerized in the same manner as in polymerization method 1, except that a both-terminal hydroxyl-hydrogenated polybutadiene represented by formula (5) was used instead of the both-terminal hydroxyl-hydrogenated polybutadiene represented by formula (4), and the terminals of the block copolymer were stabilized in the same manner as in terminal stabilization treatment 1, to obtain a modified polyacetal II-7. The number average molecular weight (Mn1) of the obtained modified polyacetal II-7, the number average molecular weight (Mn2) of the modified segment, the ratio of the number average molecular weight (Mn2) of the modified segment (B) to the number average molecular weight (Mn1) of the modified polyacetal (Mn2 / Mn1×100(%)), and the ratio of oxyethylene units in the polyacetal segment (A) are shown in Table 4. [ka] (In the formula, x and y indicate the ratio of each unit and do not indicate the bonding state. Each of x and y is an integer of 1 to 50.)

[0145] [Production of modified polyacetal II-8] A block copolymer was polymerized in the same manner as in polymerization method 1, except that a single-terminated hydroxyl-hydrogenated polybutadiene represented by formula (6) was used instead of the both-terminated hydroxyl-hydrogenated polybutadiene represented by formula (4), and the terminals of the block copolymer were stabilized in the same manner as in terminal stabilization treatment 1, to obtain a modified polyacetal II-8. The number average molecular weight (Mn1) of the obtained modified polyacetal II-8, the number average molecular weight (Mn2) of the modified segment, the ratio of the number average molecular weight (Mn2) of the modified segment (B) to the number average molecular weight (Mn1) of the modified polyacetal (Mn2 / Mn1×100(%)), and the ratio of oxyethylene units in the polyacetal segment (A) are shown in Table 4. [ka] (In the formula, o, p, and q indicate the ratio of each unit and do not indicate the bonding state. Each of o, p, and q is an integer of 1 to 50.)

[0146] [Production of modified polyacetal II-11] Modified polyacetal II-11 was obtained by carrying out polymerization and terminal stabilization in the same manner as in modified polyacetal II-1, except that a polybutadiene having hydroxyl groups at both ends and represented by formula (4) and having a number average molecular weight of 20,000 was used. The number average molecular weight (Mn1) of the obtained modified polyacetal II-11, the number average molecular weight (Mn2) of the modified segment, the ratio of the number average molecular weight (Mn2) of the modified segment (B) to the number average molecular weight (Mn1) of the modified polyacetal (Mn2 / Mn1×100(%)), and the ratio of oxyethylene units in the polyacetal segment (A) are shown in Table 4.

[0147] [Production of modified polyacetal II-12] Modified polyacetal II-12 was obtained by carrying out polymerization and terminal stabilization in the same manner as for modified polyacetal II-1, except that a polybutadiene having hydroxyl groups at both ends and represented by formula (4) and having a number average molecular weight of 230 was used. The number average molecular weight (Mn1) of the obtained modified polyacetal II-12, the number average molecular weight (Mn2) of the modified segment, the ratio of the number average molecular weight (Mn2) of the modified segment (B) to the number average molecular weight (Mn1) of the modified polyacetal (Mn2 / Mn1×100(%)), and the ratio of oxyethylene units in the polyacetal segment (A) are shown in Table 4.

[0148] [Production of unmodified polyacetal II-1] Unmodified polyacetal II-1 was obtained by carrying out polymerization and terminal stabilization in the same manner as in the production of modified polyacetal II-1, except that an equimolar amount of methanol was used instead of the hydrogenated polybutadiene having hydroxylated ends at both ends.

[0149] [Production of polyacetal mixture] 0.05 parts by mass of nylon 66 and 0.3 parts by mass of calcium stearate were uniformly added and mixed with 100 parts by mass of the modified polyacetal, and the mixture was fed to a vented twin-screw extruder (L / D=40) set at 200°C, and pelletized while degassing under reduced pressure at 90 kPa. The mixture was then dried at 100°C for 2 hours to obtain modified polyacetal mixtures II-1 to II-14. Moreover, unmodified polyacetal mixture II-15 was obtained by blending additives in the same manner as above, except that 100 parts by mass of unmodified polyacetal was used instead of the modified polyacetal.

[0150] [Production of inorganic powder injection molding composition for acid degreasing] The modified polyacetal mixtures II-1 to II-14, polypropylene (Sumitomo Noblen U501E1, Sumitomo Chemical Co., Ltd.) having an MFR of 120 g / 10 min under the conditions of 230 °C and 2.16 kg as a polyolefin having an MFR of 60 g / 10 min or more, and polytetramethylene ether glycol (PTMG3000, Mitsubishi Chemical Co., Ltd.) as a flowability imparting agent were added to an MS-type pressure kneader (DS3-10 model, manufactured by Nihon Spindle Mfg. Co., Ltd.) heated to 170 °C in such amounts that the amounts were 79 mass %, 14 mass %, and 7 mass %, respectively, relative to 100 mass % of the organic binder, and the mixture was kneaded for 30 minutes. Next, SUS316L (DAP316L, manufactured by Daido Steel Co., Ltd., melting point 1380° C., average particle size 10 μm) as a sinterable inorganic powder was added so as to be 93 mass % of the total weight of the inorganic powder injection molding composition, and kneaded for 60 minutes. The obtained kneaded mixture was put into a Wheeley type pulverizer (manufactured by Yoshida Seisakusho) and pulverized to obtain compositions for inorganic powder injection molding II-1 to II-14. Moreover, polypropylene, polytetramethylene ether glycol, and SUS316L were mixed in the same manner, except that the unmodified polyacetal mixture 1 was used instead of the modified polyacetal mixtures II-1 to II-14, to obtain an inorganic powder injection molding composition II-15. Further, an inorganic powder injection molding composition II-16 was obtained in the same manner as in Example 1, except that polyethylene glycol (PEG8000, manufactured by Aldrich) was used as a flowability imparting agent.

[0151] [Production of composition for injection molding of inorganic powder for thermal degreasing] The modified polyacetal mixtures II-1 to II-14, polypropylene (Sumitomo Noblen U501E1, Sumitomo Chemical Co., Ltd.) having an MFR of 120 g / 10 min under conditions of 230 °C and 2.16 kg of polyolefin having an MFR of 60 g / 10 min or more, and paraffin wax (PW145, Nippon Seiro Co., Ltd.) as a flowability imparting agent were added to an MS-type pressure kneader (DS3-10 model, Nippon Spindle Mfg. Co., Ltd.) heated to 170 °C in such amounts that the amounts were 25 mass %, 25 mass %, and 50 mass %, respectively, relative to 100 mass % of the organic binder, and the mixture was kneaded for 30 minutes. Next, SUS316L (DAP316L, manufactured by Daido Steel Co., Ltd., melting point 1380° C., average particle size 10 μm) as a sinterable inorganic powder was added so as to be 93 mass % of the total weight of the inorganic powder injection molding composition, and kneaded for 60 minutes. The obtained kneaded products were fed into a Wheeley type pulverizer (manufactured by Yoshida Seisakusho) and pulverized to obtain compositions for inorganic powder injection molding II-17 to II-30. Moreover, polypropylene, paraffin wax and SUS316L were mixed in the same manner, except that the unmodified polyacetal mixture II-1 was used instead of the modified polyacetal mixtures II-1 to II-14, to obtain an inorganic powder injection molding composition II-31. In addition, an inorganic powder injection molding composition II-32 was obtained in the same manner as in Example II-17, except that 40 mass% of paraffin wax (PW145, manufactured by Nippon Seiro Co., Ltd.) and 10 mass% of polytetramethylene ether glycol (PTMG3000, manufactured by Mitsubishi Chemical Corporation) were used as flow-imparting agents.

[0152] [evaluation] 1. Evaluation of thermal stability of polyacetal The weight average molecular weight (Mw1) of the modified polyacetal and the unmodified polyacetal was measured by gel permeation chromatography (HLC-8120, manufactured by Tosoh Corporation). 50 g of the composition for inorganic powder injection molding was subjected to Soxhlet extraction using 120 mL of chloroform at 80°C for 8 hours. The residue was then vacuum dried at 50°C for 3 hours, and the modified polyacetal was extracted using hexafluoroisopropanol. The weight average molecular weight (Mw2) of the resulting modified polyacetal and unmodified polyacetal was measured using gel permeation chromatography. From the obtained molecular weight, the thermal stability of the modified polyacetal or unmodified polyacetal was determined as the polyacetal molecular weight reduction rate represented by the following formula (7). The results are shown in Tables 5 and 6. Polyacetal molecular weight reduction rate (%) = (1-Mw2 / Mw1) x 100 (7)

[0153] 2. Evaluation of Injection Molding Properties of Inorganic Powder Injection Molding Compositions Using an injection molding machine (ROBOSHOT α-50iA manufactured by Fanuc), molding was performed at a molding temperature of 175 to 200°C to obtain dumbbell-shaped green molded test pieces conforming to ISO 10724-1. The test pieces were visually observed for deformation, and were judged as good if no deformation was observed, and as bad if deformation was observed. The results are shown in Tables 5 and 6.

[0154] 3. Observation of sintered body [Acid degreasing and sintering] The above-mentioned green compact test piece was supported at two points with an interval of 50 mm and set in a degreasing furnace. The above-mentioned furnace was heated to 110°C and replaced with nitrogen gas at 500 l / h for 30 minutes. After that, 30 ml / h of 98% nitric acid was supplied while maintaining nitrogen purging. Nitric acid was supplied for 2.5 hours, and then the furnace was replaced with nitrogen gas at 500 l / h for 45 minutes and cooled to room temperature for degreasing. The degreased green body was then transferred to a sintering furnace, and the inside of the furnace was replaced with argon gas, after which the temperature was raised from room temperature to 600°C at a rate of 5°C / min. After holding at 600°C for 1 hour, the temperature was raised to 1350°C at a rate of 5°C / min under reduced pressure of 1 to 5 Torr, and held for 1 hour to perform sintering, and then cooled to room temperature. The appearance of the obtained sintered body was visually observed, and those without cracks or bulges were judged as good, and those with cracks or bulges were judged as poor. The results are shown in Table 5. For samples that were visually free of cracks and blisters, they were left to stand for 24 hours at room temperature of 23°C and humidity of 50% RH, and then their weights were measured. The samples were then left to stand in water for 24 hours, and their weights were measured in water. The samples were then removed from the water, the moisture was wiped off, and their weights were measured. The density was calculated using these weights, and the density of the SUS316L used (7.8 g / cm 3 The ratio (%) of the total number of samples was calculated. The results are shown in Table 5.

[0155] [Heating debinding and sintering] The above molded body was supported at two points with an interval of 50 mm and set in a degreasing furnace. Next, the inside of the degreasing furnace was purged with nitrogen gas, and the inside of the degreasing furnace was heated to 500 ° C. at a heating rate of 30 ° C. / hr as a first condition and a heating rate of 45 ° C. / hr as a second condition, and degreasing was performed by holding at 500 ° C. for 2 hours. Next, the degreasing molded body was transferred to a sintering furnace, and after replacing the inside of the furnace with argon gas, the temperature was raised from room temperature to 600 ° C. at a condition of 5 ° C. / min. After holding at 600 ° C. for 1 hour, the temperature was raised to 1350 ° C. at a condition of 5 ° C. / min under a reduced pressure of 1 to 5 Torr, and sintered by holding for 1 hour, and then cooled to room temperature. The appearance of the obtained sintered body was visually observed, and those without cracks or bulges were judged as good, and those with cracks or bulges were judged as poor. The results are shown in Table 6. For samples that were visually free of cracks and blisters, they were left to stand for 24 hours at room temperature of 23°C and humidity of 50% RH, and then their weights were measured. The samples were then left to stand in water for 24 hours, and their weights were measured in water. The samples were then removed from the water, the moisture was wiped off, and their weights were measured. The density was calculated using these weights, and the density of the SUS316L used (7.8 g / cm 3 The ratio (%) of the total number of samples was calculated. The results are shown in Table 6.

[0156] [Table 4]

[0157] [Table 5]

[0158] [Table 6] [Industrial Applicability]

[0159] The composition for inorganic powder injection molding of the present invention is suitable for inorganic powder injection molding applications.

Claims

1. a sinterable inorganic powder; An organic binder including a modified polyacetal (C) having a polyacetal segment (A) and a modified segment (B); An inorganic powder injection molding composition comprising: the modified polyacetal (C) has a melt flow rate (MFR) measured under conditions of 190° C. and 2.16 kg of 70 g / 10 min or more and 160 g / 10 min or less; The modified segment (B) has a number average molecular weight of 500 to 10,000; The modified segment (B) is a hydrogenated polybutadiene.

1. A composition for inorganic powder injection molding comprising:

2. 2. The inorganic powder injection molding composition according to claim 1, wherein the modified polyacetal (C) has a number average molecular weight of 10,000 to 50,000.

3. 3. The inorganic powder injection molding composition according to claim 1, wherein the polyacetal segment (A) comprises 95.0 to 99.9 mol % of oxymethylene units and 0.1 to 5.0 mol % of oxyalkylene units represented by formula (1). 【Chemistry 1】 (In the formula, each R is independently selected from a hydrogen atom, an alkyl group, a substituted alkyl group, an aryl group, and a substituted aryl group, and m is an integer selected from 2 to 6.)

4. 3. The inorganic powder injection molding composition according to claim 1, wherein the modified polyacetal (C) is a block copolymer represented by (A)-(B)-(A).

5. The inorganic powder injection molding composition according to claim 1 or 2, further comprising a lubricant.

6. An inorganic powder injection molding composition as described in claim 1 or 2, wherein the mass proportion of the polyolefin resin in the organic binder is 2 mass% or less relative to 100 mass% of the organic binder.

7. The inorganic powder injection molding composition of claim 1, wherein the sinterable inorganic powder is selected from metal powders, alloy powders, metal carbonyl powders, ceramic powders and mixtures thereof.

8. The inorganic powder injection molding composition described in claim 5, wherein the mass ratio of the lubricant is 5 to 60 mass % relative to 100 mass % of the organic binder.

9. An injection molded article comprising the inorganic powder injection molding composition according to claim 1 or 2.

10. A sintered body obtained by degreasing and sintering the injection molded body according to claim 9.

11. a sinterable inorganic powder; An organic binder including a modified polyacetal (C) having a polyacetal segment (A) and a modified segment (B); An inorganic powder injection molding composition comprising: The modified polyacetal (C) has a number average molecular weight of 10,000 to 500,000; The modified segment (B) has a number average molecular weight of 500 to 10,000; The modified segment (B) is a hydrogenated polybutadiene, the polyacetal segment (A) is composed of 95.0 to 99.9 mol % of oxymethylene units and 0.1 to 5.0 mol % of oxyalkylene units represented by formula (1); a ratio (Mn2 / Mn1×100(%)) of the number average molecular weight (Mn2) of the modified segment (B) to the number average molecular weight (Mn1) of the modified polyacetal (C) is 0.5% or more and 10% or less; 1. A composition for inorganic powder injection molding comprising: 【Chemistry 2】 (In the formula, each R is independently selected from the group consisting of a hydrogen atom, an alkyl group, a substituted alkyl group, an aryl group, and a substituted aryl group, and m is an integer selected from 2 to 6.)

12. The inorganic powder injection molding composition according to claim 11, wherein the modified polyacetal (C) is a block copolymer represented by (A)-(B)-(A).

13. 13. The composition for inorganic powder injection molding according to claim 11 or 12, wherein a polyacetal molecular weight reduction rate of a weight average molecular weight of a modified polyacetal obtained by extracting the composition for inorganic powder injection molding in chloroform at 80° C. for 8 hours relative to the weight average molecular weight of the modified polyacetal (C) is 40% or less.

14. The inorganic powder injection molding composition according to claim 11 or 12, comprising a polyolefin resin having a melt flow rate (MFR) of 60 g / 10 min or more measured under conditions of 230° C. and 2.16 kg.

15. The inorganic powder injection molding composition of claim 11 or 12, wherein the sinterable inorganic powder is selected from metal powders, alloy powders, metal carbonyl powders, ceramic powders and mixtures thereof.

16. An injection molded article comprising the inorganic powder injection molding composition according to claim 11 or 12.

17. A sintered body obtained by degreasing and sintering the injection molded body according to claim 16.

Citation Information

Patent Citations

  • Composition for producing sintered molded body

    JP1997111306A

  • Composition for manufacturing sintered molding

    JP2001106581A

  • Composition for manufacturing sintered molding

    JP2002029856A

  • Formation for powder compacting and degreasing method of compacted product using it

    JP2004076153A

  • Thermoplastic material containing binder for producing metal moldings

    JP2009542880A